Implementasi Pembelajaran E-learning Bahasa Inggris di SMPN 1 Pangkalpinang - Cakrawala, Cakrawala; Novrieta, Dina (LENTERNAL: Learning and Teaching Journal, 2024)
The Corona Virus Disease Covid-19 outbreak has presented its own challenges for educational institutions, especially formal education from basic education to tertiary level. Educational institutions should be free from outbreaks or starting viruses. from the cleanliness of the school, classes, equipment or facilities used for learning must be clean and the facilities and infrastructure complete according to needs. However, with the sudden arrival of the Covid-19 outbreak, the world of Indonesian education needs to follow a path that can help school conditions in an emergency. Schools need to force themselves to use online media. However, the use of technology is not without problems, there are many variants of problems that hinder the implementation of effective learning using online methods. This study aims to find out the implementation of E-learning to English learning at SMPN 1 Pangkal Pinang. There are three components of E-Learning, namely technology, content, and learning design. These three components should be fulfilled because if one of these components is not there it is no longer E-Learning. Teachers can deliver material via Google Classroom with available features such as sharing learning videos, materials, sounds, PowerPoint, and other learning components obtained from the Internet. So students can download it. The type of research used in this research was research with a qualitative type approach that uses a descriptive qualitative method using Interviews and Documentation. The implementation of the online learning system using Google Classroom at SMPN 1 Pangkal has gone well. Running in accordance with the program from the government, supported by teachers who are responsible for daily implementation at school, they are quite good at carrying out the learning process, although there are still pluses during the learning process.